PENGARUH PRIVATE LABEL DAN KUALITAS PRODUK TERHADAP NIAT PEMBELIAN PRODUK BERMEREK “SS” DI SPESIAL SAMBAL CAB.WONOGIRI - Rizky Ramadhan Aprian Aditama; Sunarso Sunarso; Naili Amalia (ITB AAS Indonesia Surakarta, 2024)
This study aims to determine the extent to which Private Label (X1) and Product Quality (X2) influence Purchase Decision (Y). The study uses a quantitative approach with sampling using the Non-Probability Sampling method. The type of data used in this study is primary data obtained from questionnaires filled out directly by respondents. Secondary data comes from books, journals, research results, practical work reports, and related to the author's research object. In this study, the population that will be taken is all consumers of Spesial Sambal Wonogiri branch, which is immeasurable. Sample measurement is determined by using the Minimum Sample Size Determination formula for SEM according to Hair et al (2010): (Number of indicators + number of latent variables) x (5 to 10 times) Based on these guidelines, the maximum sample size for this study is: Maximum sample = (17 + 3) x 5 = 100 respondents. The analysis technique used to process and discuss the data and test the hypotheses in this study is multiple regression analysis using the SPSS application tool. Meanwhile, to assess consumer responses to the indicators, the author uses the Likert scale. The analysis tool used is multiple linear regression analysis. Using the SPSS analysis tool, the results of the study show that private label (X1) and product quality (X2), both partially and simultaneously, influence Purchase Decision (Y). Keywords : Private Label, Product Quality, influence Purchase Decision (Y)